CORONAVIRUS DISEASE 2019 (COVID-19) - Aysha Azhar (Journal of University Medical & Dental College, 2020)
Editorial CORONAVIRUS DISEASE 2019 (COVID-19) The epidemic of 2019 novel coronavirus (2019-nCoV) has been emerged from a major city named Wuhan in the Hubei Province of China. It appears to have the potential to cause a major health problem globally. Earlier it is called 2019-nCoV but now this virus is taxonomically termed SARS-CoV-2. World Health Organization has named it as “coronavirus disease 2019” and abbreviated “COVID-19” [1]. A large family of viruses named coronavirus which are classified into 4 types of genera (α, β, γ, δ). These are present in various animal species which includes bats, camels, masked palm civets, cattle, mice, dogs, cats and even in humans. The animal coronaviruses may infect and then spread among people. Similar to other two pathogenic coronaviruses, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome Coronavirus (MERS-CoV), the COVID-19 virus is a beta-coronavirus. They cause respiratory disease (viral pneumonia) which even results in death. All such coronaviruses have their origins in the bats. Viral genomic sequences of infected subjects in U.S. are similar to Chinese patients which suggest expected single, recent emergence of this virus from an animal reservoir[2,3]. Many affected patients of COVID-19 outbreak in Wuhan, showed indication with the large live animal market or wet market. It indicated animal to person spread. Later reports did not mention exposure to wet markets which indicated persontoperson spread. Other countries including United States have also been reported person to person spread.COVID-19 transmission possibly happens through means of large droplets and contact. It is also transmitted by means of aerosols and fomites [4]. Zhu et al. have been sequenced the viral genome of novel coronavirus. Their results were in conjunction with other reports which showed 75 to 80% identical sequence with the SARS-CoV. Such findings also confirmed more close relation with numerous bat coronaviruses. It is also noted that SARS-CoV-2 grows better in primary human airway epithelial cells [5]. The prominent aspect of COVID-19 epidemic is fear. This feature is playing a devastating role in daily life, social and economics. Development is still going on for preparing specific anticoronaviral therapies. There is no vaccine for COVID-19 yet. We have better understanding now for how to control such infections in the community. This understanding must alleviate some of the novel virus fear. Regarding the people health measures, it includes isolation of the affected patients in the community. In time diagnosis and stringent observance to the universal precautions are important in preventing and controlling of COVID-19. To create awareness for prevention is the best strategy to protect ourselves in an outbreak. It includes the importance of hand washing, avoid touching face, cough or sneeze into a tissue or cloth, stay away from infected people and places. Wear a face mask if you are sick and stay at home. It is hoped that such precautions must be supportive in reducing transmission of the novel human coronavirus. REFERENCES: WHO. Clinical management of severe acute respiratory infectionwhen novel coronavirus (nCoV) infection is suspected. [Internet] 2020, [cited on 19 Jan 2020]. Available from: https://www.who.int/internal-publications-detail/clinicalmanagement-of-severe-acute-respiratory-infection-when-novelcoronavirus-(ncov)-infection-is-suspected. Perlman S. Another decade, another coronavirus. New Englandjournal of medicine. 2020; 382:760-762. DOI: 10.1056/NEJMe2001126. Chu DK, Pan Y, Cheng SM, Hui KP, Krishnan P, Liu Y, et al. Molecular diagnosis of a novel coronavirus (2019-nCoV) causing an outbreak of pneumonia. Clinical chemistry. 2020;66(4):549-55. DOI: 10.1093/clinchem/hvaa029. Huang C, Wang Y, Li X, Ren L, Zhao J, Hu Y, et al. Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China. The lancet. 2020;395(10223):497-506.DOI:10.1016/S0140-6736(20)30183-5 Zhu N, Zhang D, Wang W, Li X, Yang B, Song J, et al. A novel coronavirus from patients with pneumonia in China, 2019. New England Journal of Medicine. 2020;382:727-733. DOI: 10.1056/NEJMoa2001017.